Effects of Ge Doping on the AC Susceptibility and Electrical Properties of Tl(Ba,Sr)CaCu2O7 Superconductor - Ilhamsyah A.B.P.; Mujaini M.; Mohamed H.; Abd-Shukor R. (Springer, 2024)
The TlSr2CaCu2O7 ceramic is not easily prepared in the superconducting form but superconducts at higher temperatures than TlBa2CaCu2O7 with proper elemental substitutions. The combination of Ba and Sr in Tl(Ba,Sr)CaCu2O7 with a suitable elemental substitution is an interesting topic to study. In this paper, the effects of Ge on the superconductivity of Tl1-xGe xBaSrCaCu2O7 for x = 0 to 0.6 are reported. The samples were prepared via the conventional solid-state reaction method. Powder X-ray diffraction patterns revealed a single Tl-1212 phase for the x = 00.2 samples. The electrical resistance versus temperature curves showed metallic normal state behavior for all samples with onset transition temperature Tc-onset between 90 and 100K and zero transition temperature Tc-zero between 67 and 81K. Ge-doping suppressed Tc-onset and the AC susceptibility transition temperature, Tc? but enhanced Tc-zero and narrowed the transition width ?Tc. The x = 0.3 sample showed the highest Tp indicating the improvement of the intergrain coupling. Tp is the peak temperature of the imaginary part, ? of the complex susceptibility. The intergrain critical current density, Jc at the peak temperature Tp for all samples was between 15 and 18 A cm?2. Lower doping of Ge increased the homogeneities of the individual superconducting grains and enhanced intergrain coupling. The role of ionic radius and GeO2/CuO2 layers on the superconductivity of Tl(Ba,Sr)CaCu2O7 are discussed. 2023, This is a U.S. Government work and not under copyright protection in the US